2016
DOI: 10.1021/acs.est.6b02247
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Lithium from Wastewater Using a Fixed Bed Packed with 3-D MnO2 Ion Cages

Abstract: 3-D MnO 2 ion cages (CMO) were fabricated and shown to have a high capacity for lithium removal from wastewater. CMO had a maximum Li(I) adsorption capacity of 56.87 mg/g, which is 1.38 times greater than the highest reported value (41.36 mg/g). X-ray photoelectron spectroscopy indicated that the stability of the −Mn−O−Mn−O− skeleton played an essential role in Li adsorption. The lattice clearance had a high charge density, forming a strong electrostatic field. The DubininAshtakhov (DA) site energy distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…Based on the literatures, adsorption mechanism is consisted of redox reactions 43,44 and ion exchange. 45 There is no valence change of Ti aer Li + adsorption (Fig. 13c), indicating that the Li + adsorption on H 4 Ti 5 O 12 is an ion exchange reaction which matches well with the Dubinin-Radushkevich isotherm model.…”
Section: Materials Characterizationsupporting
confidence: 66%
“…Based on the literatures, adsorption mechanism is consisted of redox reactions 43,44 and ion exchange. 45 There is no valence change of Ti aer Li + adsorption (Fig. 13c), indicating that the Li + adsorption on H 4 Ti 5 O 12 is an ion exchange reaction which matches well with the Dubinin-Radushkevich isotherm model.…”
Section: Materials Characterizationsupporting
confidence: 66%
“…However, according to some recent studies, the adsorption affinity of MnO 2 towards Pb(II) was highly related to the structures and surface properties of MnO 2 . Luo et al 16 studied adsorptive removal of lithium by 3D-MnO 2 from wastewater and found that 3D-MnO 2 with high degree of porosity and large pores exhibited a higher adsorption capacity than 1D-MnO 2 . Kozlova et al 17 prepared complex manganese oxides with different sizes of structural tunnels, and concluded that the tunnel size was the determining factor for the sorption of heavy metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…The high commercial values of Li as well as Rb result in explosive demand of them . However, the extraction of Li(I) and Rb(I) is faced with so many problems because of their unique physical and chemical properties . Therefore, the efficient extraction of Li(I) and Rb(I) is of urgent task from an environmental perspective and a commercial perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficient extraction of Li(I) and Rb(I) is of urgent task from an environmental perspective and a commercial perspective. Luo et al fabricated 3‐D MnO 2 ion cages (CMO), which exhibited a high capacity for lithium removal from wastewater. It is generally known that cyclic ethers can coordinate with metal ions to form more stable complexes compared with corresponding open chain analogues, and this is the so‐called “macrocyclic effect”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation